2023
DOI: 10.3390/ijms241311194
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling of the Dura Mater in Patients with Moyamoya Angiopathy

Abstract: Moyamoya angiopathy (MMA) is an uncommon cerebrovascular disease characterized by a progressive steno-occlusive lesion of the internal carotid artery and the compensatory development of an unstable network of collateral vessels. These vascular hallmarks are responsible for recurrent ischemic/hemorrhagic strokes. Surgical treatment represents the preferred procedure for MMA patients, and indirect revascularization may induce a spontaneous angiogenesis between the brain surface and dura mater (DM), whose functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…In this regard, multi‐omic approaches may turn out to be crucial in patients’ risk stratification and precision medicine, allowing for the selection and customization of medical treatment based on individual signatures. In addition, combining multiple omics strategies may also shed light on potential novel targets for MMD therapeutic intervention, as shown above for FLNA and LPC 6,7,10 …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, multi‐omic approaches may turn out to be crucial in patients’ risk stratification and precision medicine, allowing for the selection and customization of medical treatment based on individual signatures. In addition, combining multiple omics strategies may also shed light on potential novel targets for MMD therapeutic intervention, as shown above for FLNA and LPC 6,7,10 …”
Section: Figurementioning
confidence: 99%
“…Interestingly, the quantitative analysis revealed that Filamin A (FLNA) was significantly up‐regulated in all MMD subgroups when compared to control subjects. Such evidence is particularly relevant if considering the results obtained through a comprehensive, label‐free, quantitative MS‐based proteomic characterization of dura mater samples from MMD patients 7 . Indeed, exactly FLNA emerged among the most abundant detected proteins and was indicated as a second hit gene in MMD pathogenesis, by promoting MMD‐like vascular formation.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of haptoglobin and A1BG in MMD patients' cerebrospinal fluid suggests potential roles in inflammation and angiogenesis, making them promising novel biomarkers for further investigation [ 21 ]. Moreover, serum proteomics has revealed dysregulated lipid metabolism in both ischemic and hemorrhagic MMD patients, emphasizing its significance in vascular changes [ 22 ].In addition, the characterization of proteins in Moyamoya angiopathy (MMA) between the brain surface and dura mater has identified Filamin A as a potential key player, offering initial insights into MMA’s unique intracranial vasculopathy [ 23 ]. Investigation into RNF213’s role in MMD and antimicrobial activity has highlighted changes in proteins like MVP, CYR61, and DDAH1 upon RNF213 knockdown, suggesting potential connections between RNF213, immune responses, and MMD development, possibly involving nitric oxide production in combating Listeria infection [ 24 ].…”
Section: Proteomicsmentioning
confidence: 99%